2015
DOI: 10.1371/journal.pone.0120636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Leydig Cell Function on the Ratio of the Second to Fourth Digit Lengths in School-Aged Children

Abstract: Prenatal sex hormones can induce abnormalities in the reproductive system and adversely impact on genital development. We investigated whether sex hormones in cord blood influenced the ratio of the second to fourth digit lengths (2D/4D) in school-aged children. Of the 514 children who participated in a prospective cohort study on birth in Sapporo between 2002 and 2005, the following sex hormone levels were measured in 294 stored cord blood samples (135 boys and 159 girls); testosterone (T), estradiol (E), prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…3,11,12 Over the past few years, a body of work has arisen supporting a correlation between higher 2D:4D ratios and higher ratios of androgens to estrogens in the prenatal, and immediately postnatal, period (including in samples obtained from amniocenteses), 4,13,14 and specifically with prenatal Leydig cell function. 15 Beyond this period of susceptibility, while bone growth continues to be regulated by many factors including nutrition and hormonal influences, the 2D:4D ratio has been found to change only minimally, 16 appears stable with age, 17 and does not seem to be influenced with later regulatory periods such as puberty 18,19 or by adult testosterone levels. [20][21][22] Mechanistically, given reported anti-inflammatory and neuroprotective effects in animal models, 23,24 a higher androgen to estrogen ratio might have an organizing role in modulating downstream inflammatory responses.…”
Section: Ms Clinical Outcomesmentioning
confidence: 99%
“…3,11,12 Over the past few years, a body of work has arisen supporting a correlation between higher 2D:4D ratios and higher ratios of androgens to estrogens in the prenatal, and immediately postnatal, period (including in samples obtained from amniocenteses), 4,13,14 and specifically with prenatal Leydig cell function. 15 Beyond this period of susceptibility, while bone growth continues to be regulated by many factors including nutrition and hormonal influences, the 2D:4D ratio has been found to change only minimally, 16 appears stable with age, 17 and does not seem to be influenced with later regulatory periods such as puberty 18,19 or by adult testosterone levels. [20][21][22] Mechanistically, given reported anti-inflammatory and neuroprotective effects in animal models, 23,24 a higher androgen to estrogen ratio might have an organizing role in modulating downstream inflammatory responses.…”
Section: Ms Clinical Outcomesmentioning
confidence: 99%
“…Manning and Fink correctly pointed out that there are two additional studies relating to cord blood. At the time of publishing my Letter, I was unaware of the two papers by Mitsui et al [9,10]. However, I had previously contacted the lead author of Manning and Fink to ask whether he knew of any relevant studies that I had not included but he did not inform me of these.…”
mentioning
confidence: 99%
“…This means my statement "no statistically significant effects have yet been reported in male-only samples" is in fact incorrect. The first paper [9] reported on a sample of school-aged children from Japan (135 males, 159 females), and, whilst controlling for covariates, observed a negative correlation between insulin-like factor 3 (INSL3) and mean 2D:4D in males (β = −0.377, p < 0.05). Closer inspection revealed that digit ratios for the left hand (L2D:4D) were significantly correlated with INSL3 (β = −0.414, p = 0.0125) whereas those for the right hand (R2D:4D) were not.…”
mentioning
confidence: 99%
“…Although serum INSL3 is a proven marker of Leydig cell function before and after birth [Mitsui et al, 2015], it has not been assessed in DSD patients with purportedly isolated Leydig cell impairment.…”
Section: Defects Of Androgen Synthesismentioning
confidence: 99%